2015
DOI: 10.1080/07370016.2015.992266
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Metabolic Syndrome Among South Korean Adults

Abstract: This study analyzed the prevalence of metabolic syndrome (MetS) and evaluated the factors associated with MetS. Subjects numbered 2,213 adults who participated in the health screening survey. Results show that the prevalence of MetS, Risk-MetS, and Non-MetS was 28.2%, 44.9%, and 26.9% respectively. Factors influencing variables were age, gender, history of hypertension and diabetes mellitus, abdominal obesity, high-density lipoprotein cholesterol, triglyceride, blood pressure, fasting blood glucose, alcohol co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The reported prevalence range of MS varied widely from 1.6 to 29.6% in men and 10.1 to 32.8% in women [8]. The NCEP-ATP III-derived definition of MS was used in this study, and the MS prevalence was similar with that reported in other studies using the same definition [24, 25]. …”
Section: Discussionsupporting
confidence: 63%
“…The reported prevalence range of MS varied widely from 1.6 to 29.6% in men and 10.1 to 32.8% in women [8]. The NCEP-ATP III-derived definition of MS was used in this study, and the MS prevalence was similar with that reported in other studies using the same definition [24, 25]. …”
Section: Discussionsupporting
confidence: 63%
“…Each of the psychosocial variables of depression, physical activity, and smoking were related to MetS and/or other chronic diseases/syndromes (Dirik & Karanci, 2010;Park, Kim, Lee, Kang, & Hendrix, 2015;Shen, Findley, Banerjea, & Sambamoorthi, 2010). Clinical depression was related to MetS in both cross-sectional (Huang et al, 2011) and cohort (Butnoriene, Bunevicius, Norkus, & Bunevicius, 2014) studies and with individual components of MetS, including obesity (Lin, Liang, Liao, & Tsay, 2014) and elevated glucose (Luppino, Bouvy, Giltay, Penninx, & Zitman, 2014).…”
Section: Psychosocial Predictorsmentioning
confidence: 98%
“…Similar increasing trends have been observed in Europe and other countries [ 2 , 5 ]. According to the National Cholesterol Education Program’s Adult Treatment Panel III criteria, and per the World Health Organization Asia-Pacific guidelines, the prevalence of metabolic syndrome was approximately 28.2% in the general population of Korea in 2012 [ 6 ]. The mortality rate due to cardiovascular disease has increased from 35.6 to 52.4 out of 100,000 persons over 2003–2014.…”
Section: Introductionmentioning
confidence: 99%